Pengaruh Gaya Kepemimpinan Altruistik dan Supervisi Kelas untuk Meningkatkan Kepuasan Kerja Guru di SD Wilayah Siantar Naungan YPK ST. Yoseph Pematangsiantar - Sinaga, Marince; Sherly, Sherly; Herman, Herman (CV. Creative Tugu Pena, 2024)
Altruistic leadership plays an important role in shaping subordinates' positive attitudes and behavior, such as job satisfaction. This research is also motivated by a research gap in previous research which discussed leadership styles more broadly and there is still a lack of research in Indonesian that discusses altruistic leadership and its relationship with employee job satisfaction. From the results of interviews and field observations of teachers, especially in the Wialyah Siantar Elementary School unit under the auspices of YPK Santo Yoseph Pematangsiantar, job satisfaction is a factor that is greatly influenced by the type of leadership of the school principal and the leadership methods applied. So in the discussion and results of this research, altruistic leadership and its relationship to principal supervision have an influence on teacher job satisfaction. Altruistic leadership influences job satisfaction. Job satisfaction can also increase if supervision is carried out well. Keywords: Altruistic Leadership, Principal Supervision, Job Satisfaction